2010
DOI: 10.1021/je9007662
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluation of the Thermodynamic Activity Quantities in Aqueous Alkali Metal Bromide Solutions at 25 °C

Abstract: The Hückel equation used in this study to correlate the experimental activities of dilute alkali metal bromide solutions up to a molality of about 1.5 mol·kg−1 contains two parameters that are dependent on the electrolyte: B [that is related closely to the ion-size parameter (a*) in the Debye−Hückel equation] and b 1 (this parameter is the coefficient of the linear term with respect to the molality, and this coefficient is related to hydration numbers of the ions of the electrolyte). In more concentrated sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(66 citation statements)
references
References 33 publications
2
64
0
Order By: Relevance
“…Also the vapour pressure of NaNO 3 solutions is at the same molality higher than that of the KCl solution although the reverse is always true for NaCl solutions (see also reference [11]). These results show clearly that water molecules in aqueous alkali metal nitrate solutions are much less thermodynamically stabilized than in chloride solutions (or in other halide solutions, see also reference [21]). .…”
Section: Comparison Of the Recommended Activity Values To The Literatmentioning
confidence: 79%
See 4 more Smart Citations
“…Also the vapour pressure of NaNO 3 solutions is at the same molality higher than that of the KCl solution although the reverse is always true for NaCl solutions (see also reference [11]). These results show clearly that water molecules in aqueous alkali metal nitrate solutions are much less thermodynamically stabilized than in chloride solutions (or in other halide solutions, see also reference [21]). .…”
Section: Comparison Of the Recommended Activity Values To The Literatmentioning
confidence: 79%
“…In the previous studies, it was found that the following Hückel equations apply very well to the thermodynamic properties of NaCl [11], KCl [11], LiCl [19], RbCl [20], CsCl [20], and alkali metal bromide [21] solutions at least up to a molality of 1 mol Á kg À1 :…”
Section: Theorymentioning
confidence: 89%
See 3 more Smart Citations